Empowering rural communities through Banana Pseudostem utilization as alternative food - Achmad Ramadhan; Musdalifah Nurdin; Magfirah; Yandi Ary Pratama; Aldy Trianda; Aprodita Hutabarat; Imelda Puji Astuti; Hardina (University of Merdeka Malang, 2025)
This community service program was carried out in Rogo Village, Central Sulawesi, Indonesia, with the goal of empowering the local community by utilizing banana pseudostem as an alternative food source. A total of 30 participants, consisting of housewives, youth members, and micro-entrepreneurs, took part in a series of activities that included socialization, technical training on banana pseudostem chip production, basic business management, and digital marketing. The program adopted a participatory and hands-on approach, and its effectiveness was evaluated through pre-tests, post-tests, and product assessments. The findings showed a notable improvement in participants’ knowledge and skills, as the average score increased from 60.67 before training to 85.40 after training. Participants were also able to produce banana pseudostem chips that met basic taste and hygiene standards, with several beginning to market their products online via WhatsApp Business and social media. Overall, the program strengthened entrepreneurial capacity, encouraged group collaboration, and introduced a sustainable food innovation that contributes to poverty reduction, food security, and responsible consumption in line with the SDGs.